An Overview Of Phytochemical Identification Of Secondary Metabolites Ofmedicinal Plant Dactylorhiza Hatagirea - vishwakarma, Shivani; Karole, Dr. Sarita (Asian Journal of Pharmaceutical Research and Development, 2021)
Plants are a valuable source of new natural products. Despite the availability of different approaches for the discovery of therapeutically, natural products still remain as one of the best reservoirs of new structural types. The standardized extracts of plants, provide unlimited opportunities for new drug discoveries because of the unmatched availability of chemical diversity. According to the World Health Organization (WHO), more than 80% of the world’s population relies on traditional medicine for their primary healthcare needs.HPLC is a versatile, robust, and widely used technique for the isolation of natural products, HPLC is a chromatographic technique that can separate a mixture of compounds and is used in phytochemical and analytical chemistry to identify, quantify and purify the individual components of the mixture. Currently, this technique is gaining popularity among various analytical techniques as the main choice for fingerprinting study for the quality control of herbal plants. Natural products are frequently isolated following the evaluation of a relatively crude extract in a biological assay in order to fully characterize its properties. Early studies showed that Dactylorhizahatagirea root are rich source of phytochemicals including flavonoids, phenolics, alkaloids. Therefore this study was conducted with the aim to investigate phytoconstituents present in Dactylorhizahatagirea root and assessment of their antioxidant characteristics.